Is BI Rate Effective?: An Investigation of Taylor Rule Application in Indonesia - Kusuma, Vincent Jonathan; Prasetyo, Ahmad Danu Prasetyo (Journal of Business and Management, 2016)
Abstract.This research examines the effect BI rate towards the economic condition of Indonesia, measured by various variables using the Taylor Rule methods. This study has a purpose to measure the effect of BI rate to the Indonesian economics to see the effectiveness of BI rate towards Indonesian Economics. Considering the fluctuating Indonesian economics, the research seems necessary. The methodology used on the paper will be VAR (Vector Auto Regression). The type ofÂ  VAR used will be determined in the paper based on the type of the data through various tests. This paper concludes with a discussion of recommendation, and the limitations of the research. Some researcher and economic watchers have considered that BI rate ineffective because of various reasons. The results was BI rate is not significantly affect other variables in Taylor Rule and some variables like Inflation are the one significantly affect other variables.Keywords: BI rate, economics, inflation rate, Gross Domestic Product, Taylor Rule